Conhecimento dos trabalhadores da vigilância da água sobre a fluoretação das águas de abastecimento público - Kenupp, Bruna Zane (2017)
The practice of public water supply fluoridation for the control of dental caries has been globally proven over the years as being one of the most important Public Health measures and prevention of diseases of all time. The control of this measure in Brazil is carried out by the National Program for Surveillance of Water Quality for Human Consumption (Vigiagua), which avoids levels of the compounds below (absence of benefit) and above the recommended level (risk of fluorosis). The aim of this study was to verify the knowledge of Vigiagua Program workers in the municipalities of Grande Vitória, State of Espírito Santo, on the process of public water supply fluoridation and its monitorship, the importance of ensuring adequate levels of fluoride in water and the impact that these levels has on the health of the population and to discuss the Permanent Education in Health as a tool for the qualification of this professional. This is a descriptive research, of a qualitative nature, constructed through interviews using the seven technical references of the Vigiagua program in the region of Grande Vitória. There was limited knowledge on the part of legislation and objectives of fluoridation, revealing mechanistic work with little mastery of the actions they develop, besides the failure to insert these workers in the context of Permanent Education in Health. The present study indicates the vital importance of public investment in human resources, for the fulfillment of The Permanent Education policy.